AN ANALYSIS OF AFFIXES USED IN GRIMMS' FAIRY TALE THE WATER OF LIFE: MORPHOLOGICAL APPROACH - Rinawati, Rinawati (2011)
The research entitled An Analysis of Affixes Used in Grimm's Fairy Tale The Water of Life: Morphological Approach is descriptive qualitative. The objectives of this research are to find the kinds of affixes used in Grimm's Fairy Tale The Water of Life and to describe the forms and the functions of affixes used in Grimm's Fairy Tale The Water of Life. The data of this research consists of 180 English affixes used in Grimm's Fairy Tale The Water of Life. To gather the data, the researcher uses documentation method, and noting technique. In addition, the researcher uses contextual analysis method to analyze the data. Furthermore, a morphological analysis is applied as theoretical approach to do the research. The result of the study shows that the types affixes used in Grimm's Fairy Tale The Water of Life include prefix "a-" which changes verbs into adjectives, prefix "be-" which changes noun into verb, prefix "no-" which changes noun into pronoun, prefix "over-" which changes the meaning, and prefix "un-" which changes the meaning. And suffix "-ed" which indicates past participle, suffix "- en" which indicates past participle, suffix "-er" which changes verb into noun, suffix "-ess" which indicates female, suffix "-est" which indicates superlative, suffix "-ful" which changes noun into adjective, suffix "-ing" which changes verb into adjective and changes verb into noun, suffix "-less" which changes noun into adverb, suffix "-ly" which changes noun into adverb, suffix "-ment" which changes verb into noun, suffix "-ness" which changes adjective into noun, suffix "-s" which indicates plural or present tense, suffix "-ty" which changes adjective into noun and suffix "-y" which changes noun into adjectives. The researcher also finds suffix "-ed" constituting the most frequent occurrences of suffix with 69 out of 180 affixes. In conclusion, the meaning of affixes that used in the data source is indicator of changing the class of the category. At the end of analysis, the researcher finds that the addition of affixes into the word would influence either the meaning of the existing word.